2022
DOI: 10.47853/fas.2022.e49
|View full text |Cite
|
Sign up to set email alerts
|

Biak and Wakatobi reefs are the two hottest hotspots of coral reef fish diversity and abundance in the Indonesian Archipelago

Abstract: The Indonesian Archipelago has a very complex geological history, along with equatorial warm sea temperature, resulting in diverse types of coral reefs and high diversity of coral reef fish. Many livelihoods of the coastal community are dependent on coral reef fisheries. The present study aimed to determine which region and location in the Indonesian Archipelago has the most diverse and abundant coral reef fish. The archipelago was divided into four regions: the Indian Ocean, Sunda Shelf, Wallacea, and the Pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The Indonesian Through Flow, from the Pacific to the Indian Oceans, may continually bring marine larvae through Makassar and Lombok Straits, Flores Sea, Maluku (Molucca) Sea, Halmahera Sea, and the Banda Sea, in the central and eastern Indonesian Archipelago (Thompson et al, 2018). Bachtiar et al (2022) reported that herbivore fish predominant did not happen in all of the Indonesian Archipelago. Biak was the most predominant in herbivore fish, while Wakatobi was prevalent in carnivore fish.…”
Section: Resultsmentioning
confidence: 99%
“…The Indonesian Through Flow, from the Pacific to the Indian Oceans, may continually bring marine larvae through Makassar and Lombok Straits, Flores Sea, Maluku (Molucca) Sea, Halmahera Sea, and the Banda Sea, in the central and eastern Indonesian Archipelago (Thompson et al, 2018). Bachtiar et al (2022) reported that herbivore fish predominant did not happen in all of the Indonesian Archipelago. Biak was the most predominant in herbivore fish, while Wakatobi was prevalent in carnivore fish.…”
Section: Resultsmentioning
confidence: 99%
“…Both MPAs were important to the surrounding fisheries industry, in which MPA plays an important role in the spillover process (emigration of adult, larva and juvenile from MPA) [18]. As mentioned by [19], Wakatobi is one of the hot spots of reef fish in Indonesia. Takabonerate has a limited diversity of coastal ecosystems (mostly consisting of reefs and seagrass), while Wakatobi offers a diverse seascape.…”
Section: Introductionmentioning
confidence: 99%